Innovation Capability and Business Growth in Culinary Small Enterprises: A Management Perspective - Maiza Fikri; Leonardus Teguh Handoyo; Sahal Hanafi; Toman Sony Tambunan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Culinary small enterprises operate in highly competitive and dynamic markets where rapid imitation, shifting consumer preferences, and technological change intensify pressures on business growth. Within this context, innovation capability has emerged as a critical managerial resource, yet empirical evidence explaining how it translates into sustainable growth remains fragmented, particularly in culinary SMEs. This study investigates the effect of innovation capability on business growth from a management perspective using an empirical quantitative research design. Data were collected through a structured questionnaire administered to owner-managers and top managers of culinary SMEs operating for at least three years in urban and semi-urban areas. Innovation capability was conceptualized as a multidimensional construct comprising product, process, marketing, and organizational innovation, while business growth was measured through perceived growth in sales, market expansion, and business scale. Data were analyzed using variance-based structural equation modeling (PLS-SEM). The findings demonstrate that innovation capability has a significant positive effect on business growth, with marketing and product innovation showing the strongest impacts. The results further reveal that managerial orientation, digital capability, and organizational learning enhance the effectiveness of innovation capability in generating sustainable growth. This study contributes to innovation and SME management literature by positioning innovation capability as a strategic, growth-enabling managerial capacity.